2021
DOI: 10.2147/ccide.s300108
|View full text |Cite
|
Sign up to set email alerts
|

Dental Visits and Predictors of Regular Attendance Among Female Schoolchildren in Dammam, Saudi Arabia

Abstract: Purpose: Regular dental visits are important for the maintenance of optimal oral health and improved quality of life. The purpose of the study was to evaluate patterns of dental visits and factors associated with routine dental attendance among female schoolchildren in Dammam, Saudi Arabia. Patients and Methods: This cross-sectional study was performed on 449 female primary schoolchildren (6-11 years old) in Dammam, Saudi Arabia. The study included clinical examination for decay in the first permanent molars i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
(52 reference statements)
7
5
0
Order By: Relevance
“…The pain or trouble of teeth and gum was the most significant common reason for rural and urban children to visit the dentist (55.7% and 54.5%, respectively). These results came in accordance with many studies conducted in different provinces and regions of Saudi Arabia [9,15,[18][19][20][21]. Furthermore, our study was consistent with Rafi et al [22], which reports that about 54.6% of rural children visit the dentist due to tooth pain.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The pain or trouble of teeth and gum was the most significant common reason for rural and urban children to visit the dentist (55.7% and 54.5%, respectively). These results came in accordance with many studies conducted in different provinces and regions of Saudi Arabia [9,15,[18][19][20][21]. Furthermore, our study was consistent with Rafi et al [22], which reports that about 54.6% of rural children visit the dentist due to tooth pain.…”
Section: Discussionsupporting
confidence: 93%
“…The common frequency of cleaning teeth among urban and rural children was once or twice daily (63.2%). Similar results were found in different research in Saudi Arabia regions [14,18,20]. The use of toothbrush with fluoridated toothpaste in our study was higher in urban and rural children (79.6%, 97.1%, and 78.7%, respectively), with no significant difference between them, which was in alignment with the results observed by Prabhu et al [14] with 69.0%.…”
Section: Discussionsupporting
confidence: 92%
“…This could be because the children who needed treatment or complained went to the dentist. This concept was supported and postulated by a few researchers [ 48 , 49 , 50 , 51 , 52 ]. Visiting the dentist not only has a therapeutic component, but the educational intervention performed by health professionals within their practice also helps promote oral health in the population [ 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 64%
“…Thomson et al [ 48 ] reported that the notion of having regular dental visits might be associated with better oral health. Children who visit the dentist on a regular basis may have better oral hygiene, fewer dental problems, and control over the number of sugary drinks they consume [ 49 ]. In the previous study, it was evident that children who visited had higher dmft scores (8.14 ± 3.12) compared to the children who had never been to the dentist in the past, who had lower dmft scores (4.71 ± 4.61).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is important to teach children and adolescents good oral health behaviors because they will carry those valuable lessons with them as they get older ( 10 ). Particularly, it is important to possess knowledge about dietary habits, brushing habits and dental visits, which will enable individuals to have good oral health ( 9 , 11 - 13 ). The results of numerous studies showed that most children brush their teeth once a day ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%